Analisis Pengelompokan Jumlah Penumpang Bus Trans Jateng Menggunakan Metode Clustering K-Means Dan Agglomerative Hierarchical Clustering (AHC) - Wicaksono, Muhammad Ryqo Jallu; Prasetyo, Sri Yulianto Joko (LPPM STIKOM Tunas Bangsa, 2024)
This study aims to analyze the clustering of Trans Jateng bus passenger numbers using the K-means clustering method and Agglomerative Hierarchical Clustering (AHC). Data on the number of Trans Jateng bus passengers from the Central Java Transportation Department is used to group passengers based on bus routes and shelters. The K-means method produces 3 clusters with different data quantities for each cluster, while AHC also produces 3 clusters with different patterns. The analysis results show that the K-means method provides more measurable results compared to the AHC method in clustering the Trans Jateng bus passenger data. The information obtained from this analysis can be used to improve Trans Jateng bus transportation services and provide useful insights for decision-makers. Thus, this research contributes to the field of public transportation data analysis and clustering techniques